Exploring the Perception and Attitude of Cardiovascular Nurses for the Prevention of Central Line Associated Blood Stream Infections: A Qualitative Study - Ma. Ana Flor C. Pascua; Majed Al Shehri; Rafael Lopez; Hanan Asiri (Journal Of Nursing Practice, 2025)
Background: Many healthcare facilities have implemented evidence-based guidelines and best practices for preventing Central line-associated bloodstream infections (CLABSI), and nurses often actively adhere to these protocols. They may collaborate with infection control teams, implement proper hand hygiene practices, use sterile techniques during catheter insertion and maintenance, and monitor patients closely for signs of infection. While most cardiovascular nurses are diligent in preventing CLABSIs, challenges may arise due to factors such as heavy workload, time constraints, staff shortages, and variations in adherence to infection control protocols among healthcare workers. Purpose: Therefore, our research study aims to explore the underlying factors contributing to the increase of CLABSI despite the availability of prevention guidelines and bundles of care in a government tertiary-military specialized cardiac center in Saudi Arabia. Accordingly, the study explored the perception and attitude of cardiovascular nurses toward preventing Central line-associated bloodstream infections (CLABSI).  Methods: This is an exploratory qualitative research study in which Prince Sultan Cardiac Center nurses participated.  An invitation link was distributed to the target participants for a focus group interview. Then, the data collected was transcribed verbatim for content analysis for repeated patterns of themes. Results: The study revealed three main themes, namely, handling (i.e., the importance of handling a central line properly for cardiac patients), competency (i.e., the need for reconsidering the evaluation frequency of management of central line competency), and actual practice (i.e., aspects related to the actual practice). Conclusion: Accordingly, several sub-themes emerged as a result. Implications of the study and recommendations were made.